Cross-sectional associations between adolescents' physical literacy, sport and exercise participation, and wellbeing - Melby, Paulina S.; Elsborg, Peter; Bentsen, Peter; Nielsen, Glen (Frontiers in Public Health, 2023)
Background Adolescence is a significant period in one's development of positive emotional and social wellbeing. Physical literacy (PL) is considered a determinant of physical health and wellbeing and is thought to be the foundation for an individual's engagement in physical activities. Yet, limited evidence exists on PL's association with adolescents' health and physical activity behavior. This study aims to (1) explore the associations between Danish adolescents' PL and their emotional and social wellbeing, (2) examine whether these associations are mediated by sport and exercise participation (SEP), and (3) consider if the associations differ across sex. Methods Cross-sectional data from a national population survey were collected in 2020. The sample consisted of 1,518 Danish adolescents aged 13–15 years. PL was assessed with the validated MyPL questionnaire. The weekly time engaged in sports and exercise was self-reported. Self-esteem, life satisfaction, body satisfaction, and loneliness were measured with items from the standardized HBSC questionnaire, and a wellbeing composite score was calculated from these four measures. We constructed structural equation models with PL and sports and exercise participation as independent variables and the five aspects of wellbeing as dependent variables. Results Positive associations were observed between PL and SEP (β = 0.33, p < 0.001) and between PL and the five aspects of wellbeing with β-values between 0.19 and 0.30 (p < 0.001). These associations were greater among girls. The association between PL and four of the five wellbeing outcomes were partly mediated by SEP with indirect effects (β) between 0.03 and 0.05. Conclusions Results from this study support the hypotheses that PL is important for children and adolescents' wellbeing and physical activity behavior.